Timeliness Of Financial Statements Submission In Industrial Era 4.0 Case study Of Chemical Sector Companies - Wijayanti, Iin (STIE PGRI Dewantara Jombang, 2020)
The purpose of this study was to determine the effect of company size, company age, leverage and profitability on the timeliness of financial statement submission. The population used in this study is the annual report of chemical sector companies listed on the Indonesia Stock Exchange of 50 financial statements. Sampling technique saturated sampling. Data analysis for hypothesis testing in this study uses multiple linear regression analysis. Based on the analysis and discussion, it can be concluded that there is a significant positive effect on company size and profitability on the timeliness of report submission. In addition, there is also a significant negative effect on the company's age and leverage on the timeliness of financial statement submission.